Marine Macrophytes as Carbon Sinks: Comparison Between Seagrasses and the Non-native Alga Halimeda incrassata in the Western Mediterranean (Mallorca) - Marx, Lukas; Flecha, Susana; Wesselmann, Marlene; Morell, Carlos; Hendriks, Iris Eline (Frontiers in Marine Science, 2021)
Seagrass species play a critical role in the mitigation of climate change by acting as valuable carbon sinks and storage sites. Another important ecosystem service of this coastal vegetation is nutrient removal. However, coastal ecosystems are under increasing pressure of global warming and associated establishment of invasive species. To elucidate the respective contributions of seagrass species Posidonia oceanica and Cymodocea nodosa and the non-native macroalga Halimeda incrassata as primary producers and nutrient sinks in coastal habitats we conducted in-situ incubations in the North-western Mediterranean Sea. Measured metabolic activity and nutrient removal as well as calcification rates in these habitats over a 24 h period in spring and summer confirmed that the endemic seagrass P. oceanica represents a valuable ecosystem with high O2 production and considerable carbon capture. The documented regression of P. oceanica meadows with higher temperatures and decline in autotrophy as measured here causes concern for the continuity of ecosystem services rendered by this habitat throughout the Mediterranean Sea with progressing climate warming. In contrast, the enhanced performance of C. nodosa and the calcifying alga H. incrassata with increasing temperatures, under expected rates of future warming is uncertain to mitigate loss of productivity in case of a potential shift in marine vegetation. This could ultimately lead to a decline in ecosystem services, decreased carbon storage and mitigation of climate change. Furthermore, this study provides a first estimate for the growth rate of H. incrassata in the Mediterranean Sea, supporting evidence for the mechanism of its rapid extension.